The Effect of Liquidity, Profitability, Activity and Leverage on Stock Returns in Food and Beverage Sub-Sector Companies Listed on the Indonesia Stock Exchange for the 2016-2020 Period - Alvarido Sibarani; Ruth Putri Yunita; Kosti Juliana Siregar; Beby Anastasia Panggabean; Tina Novianti Sitanggang (Budapest International Research and Critics University, 2022)
This research was investigated to determine the effect of variable X on variable Y. Sourced on the independent variables, namely Currento Ratio (CR), Return on Assets (ROA), Total Asset Turnover (TATO), Debt to Equity Ratio (DER) and the dependent variable is Return. Share. Where there are 100 total samples listed in the Food and Beverage Sub-Sector Companies Listed on the Indonesia Stock Exchange for the 2016- 2020 Period. The method used in this research is multiple linear regression analysis by SPSS program. The results of the analysis show that the T test Return on Assets has a positive effecto ono Stock Return, while the Current Ratio, Total Asset Turnover and Debt to Equity Ratio have no positive effect on Stock Return. It is different in the F test that together Current Ratio, Return on Assets, Total Asset Turnover and Debt to Equity Ratio have a positive and significant effect on Stock Return. The result of Adjusted R Square is 0.069, which means that the independent variable affects Stock Return only by 6,9% and the remaining 83,1% is influenced by other variables such as Inventory Turnover, Return on Equity Ratio, Inflation, Interest Rates ando Cash Ratio.